Research on the Correlation Between Skin Elasticity Evaluation Parameters and Age - Dandan Chen; Shipeng Yin; Xuelian Lu; Haokun Fu; Hongqi Gao; Suning Zhang (Cosmetics, 2024)
This study aims to explore the impact of aging on skin elasticity, a key biomechanical property that diminishes over time, using the Cutometer to assess viscoelastic parameters. Methods: Researchers analyzed 22 viscoelastic parameters from the facial skin of 60 women aged 18 to 70. Key Results: The findings indicate that relaxation phase parameters, particularly biological elasticity (R7), exhibited the strongest negative correlation with age (r = −0.62), signifying a notable decline in biological elasticity as women age. In contrast, maximum deformation during the first cycle (R0) and the total area under the upper curve after 10 cycles of deformation (F4) also showed significant negative correlations with age (r = −0.47, r = −0.48), suggesting that younger skin typically presents higher values. These correlations raise questions regarding practical applications, as the presence of moisturizers and emollients may alter the stratum corneum’s properties, thus impacting these measurements. Additionally, the ratio of delayed deformation to instantaneous deformation (R6) demonstrated a positive correlation with age (r = 0.49), indicating its potential as a marker for skin aging. Conclusions: This study highlights the critical role of relaxation phase parameters in accurately reflecting skin elasticity changes associated with aging. The results offer valuable insights for evaluating cosmetic efficacy, reinforcing the need for a nuanced understanding of how various parameters interact. These findings contribute to the ongoing development of more effective anti-aging treatments and products.